Method and apparatus for sensing infrared radiation - KIM DO YOUNG; SO FRANKY (2016)
Embodiments of the invention pertain to a method and apparatus for sensing infrared (IR) radiation. In a specific embodiment, a night vision device can be fabricated by depositing a few layers of organic thin films. Embodiments of the subject device can operate at voltages in the range of 10-15 Volts and have lower manufacturing costs compared to conventional night vision devices. Embodiments of the device can incorporate an organic phototransistor in series with an organic light emitting device. In a specific embodiment, all electrodes are transparent to infrared light. An IR sensing layer can be incorporated with an OLED to provide IR-to-visible color up-conversion. Improved dark current characteristics can be achieved by incorporating a poor hole transport layer material as part of the IR sensing layer. 本发明的实施例是关于种用于感应红外(IR)辐射的方法和设备。在具体实施例中，可通过沉积少许有机薄膜层来制造夜视装置。本发明装置的实施例可在10伏特至15伏特范围中的电压下操作，且本发明装置的实施例具有比传统夜视装置更低的制造成本。装置的实施例可包含与有机发光装置串联的有机光电晶体管。在具体实施例中，红外光可透过所有电极。IR感应层可与有机发光二极管(OLED)合并以提供IR到可见色彩上转换。可通过合并不良空穴